University Students' Ability in Evaluating Fake News on Social Media - Khairunissa, Khairunissa (D3 Perpustakaan Fakultas Vokasi Universitas Airlangga, 2020)
Background of the study: Social media has become a traffic information exchange, both true and false information. Therefore, social media users should not simply believe the information they received. This paper investigates the process of evaluating news on social media carried out by students in assessing the news they find on social media, and their ability to distinguish factual and false news.Purpose: It is to find out more about the process of students evaluating news on social media by assessing the news they found on social media, and how can they know which is the factual news and which is the fake news.Method: This research uses qualitative research methods with a descriptive approach. This research was conducted at Gadjah Mada University. The purposive sampling technique was chosen to be used in determining participants.Findings: Overall, participants were able to identify almost all news articles. Participants are able to identify almost all factual news articles correctly and most fake news articles correctly. Only a small portion of all news articles cannot be correctly identified by participants. Participants are better to identify factual news than fake news.Conclusion: Although participants already have experience in finding fake news on social media and have self-taught knowledge about how to distinguish fake news from reliable news, this is no guarantee that they can tell the news article they got fake news or factual news. The researcher wants to give advice to the academic library to provide training on the characteristics of reliable referral sources and to think critically in assessing information as part of student information literacy training.